Oxidants, Antioxidants and Thiol Redox Switches in the Control of Regulated Cell Death Pathways - Moran Benhar (MDPI AG, 2020)
It is well appreciated that biological reactive oxygen and nitrogen species such as hydrogen peroxide, superoxide and nitric oxide, as well as endogenous antioxidant systems, are important modulators of cell survival and death in diverse organisms and cell types. In addition, oxidative stress, nitrosative stress and dysregulated cell death are implicated in a wide variety of pathological conditions, including cancer, cardiovascular and neurological diseases. Therefore, much effort is devoted to elucidate the molecular mechanisms linking oxidant/antioxidant systems and cell death pathways. This review is focused on thiol redox modifications as a major mechanism by which oxidants and antioxidants influence specific regulated cell death pathways in mammalian cells. Growing evidence indicates that redox modifications of cysteine residues in proteins are involved in the regulation of multiple cell death modalities, including apoptosis, necroptosis and pyroptosis. In addition, recent research suggests that thiol redox switches play a role in the crosstalk between apoptotic and necrotic forms of regulated cell death. Thus, thiol-based redox circuits provide an additional layer of control that determines when and how cells die.